The transmission of bovine leukemia virus to calves occurs mostly through colostrum and milk - Daniel Lazzari Quadros; Kalinka Puhl; Vitoria Agnoletto Ribeiro; Rafael Frandoloso; Luiz Carlos Kreutz (Veterinary World)
Background and Aim: Enzootic bovine leukemia is highly prevalent in most dairy farms, and strategies to reduce both vertical and horizontal transmission are being investigated. In this study, we aimed to investigate the rate of in utero infection, transmission of bovine leukemia virus (BLV) to calves through colostrum and milk, and the effectiveness of colostrum and milk pasteurization in reducing BLV transmission to calves.